1995
DOI: 10.1136/thx.50.9.990
|View full text |Cite
|
Sign up to set email alerts
|

Lung injury in patients following thoracotomy.

Abstract: Background -Postoperative lung injury is a recognised complication of thoracotomy for which there are few data regarding incidence and outcome. Methods -In a case controlled study the notes of all adult patients who developed acute lung injury (ALI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 6 publications
1
40
1
1
Order By: Relevance
“…This in itself is a recognized precipitating factor for ARDS. Age and preoperative lung function do not appear to correlate with the development of PPO [11]. Aspiration of gastric contents in the post operative period and early-onset postoperative infection may mimic PPO, but are not in themselves risk factors.…”
Section: Other Factorsmentioning
confidence: 89%
See 4 more Smart Citations
“…This in itself is a recognized precipitating factor for ARDS. Age and preoperative lung function do not appear to correlate with the development of PPO [11]. Aspiration of gastric contents in the post operative period and early-onset postoperative infection may mimic PPO, but are not in themselves risk factors.…”
Section: Other Factorsmentioning
confidence: 89%
“…A study using the Consensus Committee Guidelines for ALI/ARDS found an overall incidence of lung injury of 7%. PPO severe enough to constitute ARDS was recorded in 5.2% of lobectomies and 4.9% of pneumonectomies, and ALI in 2.2% of lobectomies and 1.9% of pneumonectomies, with no cases of either following segmentectomy, wedge resection or open lung biopsy [11]. This was a retrospective investigation and may therefore have underestimated the number of patients who developed ALI postoperatively.…”
Section: Incidence Of Postpneumonectomy Pulmonary Oedemamentioning
confidence: 98%
See 3 more Smart Citations